Removal of pineal region teratomas using occipital transtentorial approach (OTA) technique: Case report and literature review. (2020) - Adji, Novan Krisno; Rozidi, Achmad Romy Syahrial; Zharfan, Rahmat Sayyid
Highlights: Pathological tumors originating purely from the pineal gland are very rare, which mainly found in children and adolescents. Clinical manifestations of pineal tumor mosty: visual impairment, headaches, and a decrease of cognitive and consciousness. It is recommended to install VP-shunt several days before definitive tumor surgery for ventricular decompression. The choice of technique is determined by the tumor location, pathological findings, and risk of complications. The OTA technique allows excellent views of pineal region, and access to the midline, superior vermis, and ventricle III. Abstract: Introduction: The development of improved micro-surgery techniques and neuroanesthesia has become increasingly sophisticated makes open-microsurgery tumor resection a choice for the management of the pineal region. Case presentation: An 11-year-old male with a pineal body tumor post ventriculo-peritoneal (VP) shunt, underwent tumor resection. Patients complain of headaches, relieve with medication but often recurrent, and often experience a decrease in consciousness. One month before the procedure, the patient experienced blurred vision, staggering, nausea, vomiting, and decrease of consciousness. The operation is performed with an occipital transtentorial approach (OTA) technique. During surgery, hemodynamics was relatively stable. Postoperatively, the patient underwent controlled ventilation in the intensive care room, and recover significantly within one week. Discussion: Various surgical approaches have been proposed for pineal region tumors. We review the available literature (PubMed) with 11 reported cases of pineal tumor therapy with the occipital transtentorial approach and evaluate general symptoms in clinical manifestations, histopathological features, radiological findings, and survival times to demonstrate therapeutic effectiveness. Several cases of the pineal tumor were also reported using tumor extraction by occipital transtentorial approach. Conclusion: The choice of approach is influenced by the location of the tumor, pathology findings, the neurosurgeon's comfort and consideration of the risk of complications.